Electrochemotherapy pre‐treatment in primary squamous vulvar cancer. Our preliminary experience. Issue 8 (7th June 2018) - Perrone, Anna M.; Galuppi, Andrea; Borghese, Giulia; Corti, Barbara; Ferioli, Martina; Della Gatta, Anna N.; Bovicelli, Alessandro; Morganti, Alessio G.; De Iaco, Pierandrea
Abstract : Background and Objectives: Previous studies showed a local tumor control of 80% in patients with relapsed squamous cell vulvar cancer (V‐SCC) treated with electrochemotherapy. These results encouraged electrochemotherapy use as neo‐adjuvant treatment in V‐SCC. The objective of this study was to evaluate the effectiveness of electrochemotherapy in reducing tumor burden in V‐SCC. Methods: Patients with histological diagnosis of primary V‐SCC eligible for surgery were enrolled. Following accurate mapping of all the lesions, electrochemotherapy was performed. One month after electrochemotherapy clinical response was evaluated according to RECIST criteria and the type of surgery was confirmed or modified. Adjuvant therapies were prescribed depending on stage and pathological evaluation. Results: We report the results from nine patients treated with electrochemotherapy before surgery. The median age was 64 years (range 51‐81 years). Tumor response after electrochemotherapy was observed in seven patients (77.8%) with one CR and six PR, without complications. Tumor downsizing led to more conservative surgery in six patients (66.7%). At a median follow‐up of 8 months (range 2‐32 months) all patients were alive without disease. Conclusions: Our preliminary analysis suggests that ECT is a suitable treatment in patients with V‐SCC before surgery, reducing the tumor size and the surgical resection.